Cultivating Fish with the Yumina Bumina System as a Solution to Increasing Community Productivity - Nyoman Dwika Ayu Amrita; I Dewa Gede Putra Sedana; I Wayan Arya Sugiarta; Tri Hayatining Pamungkas; Anak Agung Gede Agung Indra Prathama (Universitas Pendidikan Ganesha, 2023)
The aquaculture sector has an important role for the development of a country. Aquaculture not only plays an important role in economic growth, but also in the food security of a region. Aquaculture is important because this sector produces products or commodities that are not only of high economic value but also functionally useful. Therefore, the purpose of this community service is to provide fish farming assistance with the Yumina Bumina system to increase community productivity. Service activities begin with collecting information through interviews with related parties regarding strengths, weaknesses, opportunities and constraints in catfish farming, then proceed with counseling to Pokdakan Mina Jaya about benefits and sustainability and their impact on partner production and marketing levels. the resulting catfish. This community service activity was carried out for 2 months. The partner in this service activity is the Mina Jaya Catfish Cultivation Group located in Banjar Laplap Kauh, Penatih Dangin Puri Village, East Denpasar with 17 members. The result of this community service is that partners can apply the Yumina-Bumina technology system. The implications of this activity are business opportunities, increased income, and employment.